The causal association between inflammatory bowel disease and breast cancer: a bidirectional two-sample Mendelian randomization study - Yin, Yulai; Zhang, Xiaoyu (Frontiers in Genetics, 2024)
Objective: This Mendelian Randomization (MR) study aims to explore the potential bidirectional causal relationship between Inflammatory Bowel Disease (IBD) and Breast Cancer (BC).Materials: and Methods: We utilized genetic instruments from the summary statistics of genomewide association studies (GWAS) on IBD among individuals of European ancestry (12,882 cases and 21,770 controls) to investigate the association with breast cancer (14,910 cases and 17,588 controls) and vice versa. The primary causal estimates were obtained using the Inverse Variance Weighting Method (IVW), and the robustness of the results was evaluated through a series of sensitivity analyses.The study found a positive impact of genetically predicted IBD on breast cancer (OR=1.047; 95%CI:1.009-1.087; P=0.014); in the analysis of IBD subtypes, genetically predicted Crohn's Disease (CD) also had a positive effect on breast cancer (OR=1.044; 95%CI:1.015-1.073; P=0.002), but genetically predicted Ulcerative Colitis (UC) did not show a significant effect on breast cancer (P>0.05). The reverse Mendelian Randomization analysis indicated that genetically predicted breast cancer promoted the overall occurrence of IBD (OR=1.112; 95%CI:1.022-1.211; P=0.014); however, genetically predicted breast cancer did not show a significant correlation with IBD subtypes (CD and UC) (P>0.05). Genetic predictions indicate a positive effect of Crohn's Disease (CD) on the risk of Estrogen Receptor-Positive Breast Cancer (ER+BC), with (OR=1.021; 95%CI:1.002-1.040; P=0.002). Furthermore, a reverse Mendelian randomization analysis reveals that genetically predicted ER+BC contributes to the increased incidence of ulcerative colitis (UC), as indicated by (OR=1.098; 95%CI:1.032-1.168; P=0.003). In contrast, genetically predicted Estrogen Receptor-Negative Breast Cancer (ER-BC) has been shown to promote the overall occurrence of inflammatory bowel disease (IBD), with (OR=1.153; 95%CI:1.008-1.319; P=0.037). However, bidirectional two-sample Mendelian randomization analyses between other pairs did not reveal any significant associations (P>0.05).This study elucidates the bidirectional causal association between breast cancer and inflammatory bowel disease, highlighting the necessity of screening for IBD in breast cancer patients and for breast cancer in IBD patients in clinical settings.